The Potential of Night Jasmine (Nyctanthes arbor-tristis) Flower Extract as a Functional Ingredient in Yogurt Production: The Effects on Fermentation, Rheology, Sensory, and Antioxidant Properties of Yogurt - Pal Anil Kumar; Agarwal Aparna; Tripathi Abhishek Dutt; Khosravi-Darani Kianoush; Nandan Alisha; Tripathi Arunima; Hooda Ankita (The EuroBiotech Journal)
Nyctanthes arbour-tristis, commonly known as Harsinghar or Night Jasmine Flower (NJF), holds a prominent place in traditional medicine due to its diverse biological activities. With the growing trend of fortifying yogurt with natural herbs to enhance nutritional and health benefits, this research aimed to optimize herbal yogurt with NJF extract using response surface methodology (RSM). Twenty experiments were conducted with varying percentages of NJF extract, inoculum sizes, and temperatures. The NJF-fortified yogurt was evaluated for sensory, textural, and physicochemical analyses, along with an ESI-MS assessment of bioactive components. Results showed that properties varied with NJF extract percentage, with trial T18 (3.68% NJF extract, 1.5 ml inoculum size, and 41°C temperature) achieving the highest sensory score and acceptability, as well as superior textural and antioxidant properties compared to control yogurt. T18 was identified as the optimized product with protein-3.1%, fat-3.4%, moisture-72.8%, ash-0.87%, pH-4.65, and titratable acidity (TA)-0.72. The antioxidant activity of T18 and CY was 72.32% and 12.62%, respectively, and the total phenolic content was found to be 85.17 mg GAE/g, underscoring its potential as a health-enhancing yogurt variant.